Interdisciplinary Research Integration in Higher Education: A Case Study on the Development of an AI-Based Non-Invasive Hemoglobin Detection System - Sri Wiji Lestari; Nurdina Widanti; Wike Handini; Ahmad Raafi Haqq; Aditya Alamsyah (Postgraduate, University of Mataram, 2025)
This study examines the effectiveness of Project-Based Learning (PBL) in the development of a non-invasive hemoglobin detection system using photoplethysmography (PPG) integrated with artificial intelligence. A quasi-experimental design was applied to 26 Electrical Engineering students enrolled in Big Data Analysis, Sensor Design, and Embedded Systems courses. Students worked in groups to design, implement, and test prototypes. Data were collected through project rubrics, questionnaires, observations, and reflections, and were analyzed to determine the effectiveness index. The results revealed an overall effectiveness index of 3.8, categorized as good. The highest score was achieved in the affective aspect (4.2), reflecting strong motivation, proactive attitudes, and teamwork. Cognitive (3.9) and reflection (3.8) aspects also showed positive outcomes, while psychomotor (3.6) and product quality (3.5) remained weaker due to technical issues, including prototype accuracy and troubleshooting difficulties. The study demonstrates that PBL effectively integrates theory and practice, enhances 21st-century skills, and fosters meaningful learning experiences. Additionally, the findings highlight the potential of incorporating advanced technologies into engineering education while contributing to innovative health technology solutions for addressing malnutrition.